Two in one: the use of "deer" stone for making a statue in the Turkic period (results of photogrammetry in the archaeological and architectural complex "Burana Tower" in Kyrgyzstan) - Tishkin Alexey A.; Tabaldiev Kubatbek Sh.; Bondarenko Sergey Y. (Поволжская археология)
"Deer" stones on the territory of Kyrgyzstan are rare finds. This situation is due to several reasons. Special and systematic identification of such ancient statues has not yet been undertaken. Their context with well-known archaeological sites is not completely clear, although there is a connection with the eight-stone ring laying. The number of "deer" stones discovered and their design indicate that the western periphery of a large nomadic community that existed in Inner Asia from the end of the Bronze Age to the Early Iron Age was located in Prityanshan. There is potential for new discoveries. It is also necessary to study in detail the already known ancient statues. Such work has already begun, and this article is a continuation of the published results. An exhibit of the Archaeological and Architectural complex "Burana Tower" was used to demonstrate the use of photogrammetry. It turned out that the stone statue of the early Medieval period was made of "deer" stone. This practice was widespread in the Turkic period in Mongolia and Southern Siberia. Ancient and medieval images have been identified using photogrammetry.